Interest Rate Pass-Through, Monetary Policy Rules and Macroeconomic Stability - Claudia Kwapil; Johann Scharler (Oesterreichische Nationalbank (OeNB), 2007)
In this paper we analyze equilibrium determinacy in a sticky price model in which the pass-through from policy rates to retail interest rates is sluggish and potentially incomplete. In addition, we empirically characterize and compare the interest rate pass-through process in the euro area and the U.S. We find that if the pass-through is incomplete in the long run, the standard Taylor principle is insufficient to guarantee equilibrium determinacy. Our empirical analysis indicates that this result might be particularly relevant for bank-based financial systems as for instance that in the euro area.
Keywords: E32; E52; E58; 330; Interest Rate Pass-Through; Interest Rate Rules; Equilibrium Determinacy; Stability